IL-17 triggers PD-L1 gene transcription in NSCLC cells via TRIM31-dependent MEF2C K63-linked polyubiquitination - Shuai Ying; Ningxia Wu; Yuting Ruan; Wen Ge; Pei Ma; Tongpeng Xu; Yongqian Shu; Yingwei Wang; Wen Qiu; Chenhui Zhao (BMC Cancer)
Abstract Background Non-small cell lung cancer (NSCLC) is a disease related to inflammation. Proinflammatory cytokines such as interleukin 17 (IL-17) can induce cancer cell proliferation, metastasis and immune escape. Although NSCLC immune escape is partly due to the interaction between PD-1 and PD-L1 and PD-L1 expression can be upregulated in cancer cells upon stimulation with IL-17, the underlying mechanism of IL-17-triggered PD-L1 gene transcription in NSCLC cells remains elusive. Methods RT‒PCR, real-time PCR, and IB were used to assess the levels of PD-L1, MEF2C, and TRIM31 in NSCLC tissues as well as in IL-17–stimulated H1299 or PC9 cells. Bioinformatics analysis, luciferase assays, and ChIP were utilized to investigate the transcriptional mechanism of the PD-L1 gene. Co-IP/IB was used to examine the interaction between MEF2C and PD-L1, including MEF2C ubiquitination. IHC staining was carried out to analyse the expression of IL-17RA, MEF2C, TRIM31, and PD-L1 in NSCLC tissue arrays. The corresponding plasmids were constructed and identified. An isograft model was used to verify the findings in vitro. Results PD-L1, MEF2C and TRIM31 expression levels were increased in NSCLC tissues and NSCLC cells exposed to IL-17. Mechanistically, MEF2C could bind to the − 778 to -475 nt and − 336 to -97 nt regions of the PD-L1 promoter. TRIM31 could mediate MEF2C K63-linked polyubiquitination at Lys 25, increasing MEF2C recruitment to the PD-L1 promoter and PD-L1 gene transcription. MEF2C, TRIM31 or PD-L1 gene silencing effectively suppressed MEF2C K63-linked polyubiquitination, PD-L1 induction and NSCLC growth in mice inoculated with Lewis lung cancer (LLC) cells transfected with the corresponding shRNA and treated with IL-17. Conclusion IL-17 induces PD-L1 gene transcription in NSCLC cells through TRIM31-dependent MEF2C K63-linked polyubiquitination.